Approaching the Maqashid Sharia of Marriage from the perspective of Al-Qur'an Fiqh - Kasim, Dulsukmi; Sumanto, Dedi (Institut Agama Islam Negeri Kendari, 2025)
Placing marriage from the perspective of divine norms (Fiqh al-Qur'an) is a logical and spiritual reference that is always relevant for humans. According to the Qur'an, desires are paired with the instincts of all creatures, including humans. The confirmation is in surah Yasin/36: 36 and al-Zariyat/51: 49. The repetition of the word